Analysis of partially sulfonated low density polyethylene (LDPE) membranes as separators in microbial fuel cells. Issue 35 (19th April 2017) - Kumar, Vikash; Rudra, Ruchira; Nandy, Arpita; Hait, Subrata; Kundu, Patit Paban
Abstract : Sulfonated low density polyethylenes (LDPEs) in varied molar ratios have been analyzed as separating barriers in microbial fuel cells (MFCs) for bioelectricity production. Abstract : In the present study, sulfonated low density polyethylenes (LDPEs) in varied molar ratios have been analyzed as separating barriers in microbial fuel cells (MFCs) for bioelectricity production. LDPE sulfonation was performed with chlorosulfonic acid for 7, 15, 30, 45 and 60 minutes which revealed respective degree of sulfonation (DS) results of 9%, 12%, 15%, 10% and 7% in SPE-7, SPE-15, SPE-30, SPE-45 and SPE-60 membranes. Prolonged sulfonation (above 30 minutes) has shown additional sulfone crosslinking formation within the membrane structure, thereby reducing the respective DS in the SPE-45 and SPE-60 membranes. Enhanced membrane properties in terms of water uptake, ion-exchange capacity (IEC) and proton conductivity have been observed with an increasing DS as a result of the incorporated sulfonic acid in the membranes. In succession, respective IEC values of 0.0056, 0.015, 0.048, 0.0087 and 0.0012 meq g −1 and proton conductivities of 2.67 × 10 −7, 3.12 × 10 −6, 4.74 × 10 −5, 2.76 × 10 −7 and 2.13 × 10 −8 S cm −1 have been observed with the SPE-7, SPE-15, SPE-30, SPE-45 and SPE-60 membranes, where reduced membrane properties in the SPE-45 and SPE-60 membranes were observed with additional sulfone crosslinks being formed in the structure. The casted membranes were assembled as a membrane electrode assembly (MEA) in single chambered MFCs, where a maximum power and current density of 85.73 ± 5 mW m −2 and 355.07 ± 18 mA m −2 were observed with the SPE-30(DS 15%) membrane with an overall ∼88.67% chemical oxygen demand (COD) removal in a 30 day run. The employed electrogenic firmicutes showed marked reductions in the overall systemic resistance, depicting the relevance of sulfonated LDPE membranes in MFCs as potent separators for bio-energy conversion.